Proceedings of the 41st ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages 2014
DOI: 10.1145/2535838.2535877
|View full text |Cite
|
Sign up to set email alerts
|

Verifying eventual consistency of optimistic replication systems

Abstract: We address the verification problem of eventual consistency of optimistic replication systems. Such systems are typically used to implement distributed data structures over large scale networks. We introduce a formal definition of eventual consistency that applies to a wide class of existing implementations, including the ones using speculative executions. Then, we reduce the problem of checking eventual consistency to reachability and model checking problems. This reduction enables the use of existing verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
0
35
1
Order By: Relevance
“…In particular, it was shown that checking linearizability is an EXPSPACE-complete problem when the number of sites is bounded [3,21]. Eventual consistency has been shown to be decidable [8]. Sequential consistency was shown to be undecidable [3].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was shown that checking linearizability is an EXPSPACE-complete problem when the number of sites is bounded [3,21]. Eventual consistency has been shown to be decidable [8]. Sequential consistency was shown to be undecidable [3].…”
Section: Related Workmentioning
confidence: 99%
“…This undecidability result might be surprising, since it is known that linearizability (stronger than CC) [23] and eventual consistency (weaker than CC) [39] are decidable to verify in that same setting [3,8,21]. This result reveals an interesting aspect in the definition of causal consistency.…”
Section: Introductionmentioning
confidence: 95%
“…In [14,15], for instance, the focus was on abstract properties, while in [2] the goal was to show how to verify replication schemes that ensure only eventual consistency. However, little effort has been devoted to theoretical studies that would precisely measure the power and limitations of eventual consistency (beyond artifacts related to specific implementations).…”
Section: Related Workmentioning
confidence: 99%
“…This is true even if we only require the resulting linearizable object to be obstruction-free, whereas the eventually linearizable base objects are waitfree. (2) No set of eventually linearizable objects can boost the consensus power of simple linearizable objects like registers, i.e., help solve consensus among two processes in conjunction with linearizable registers. In short, eventually linearizable objects can neither implement linearizable ones (1) nor augment the power of shared linearizable registers (2).…”
Section: Introductionmentioning
confidence: 99%
“…[10] specifies replicated data types using relations over events and proposes a framework for verifying store implementations. On another line of research, the work in [7] focuses on criteria for decidable checking of eventual consistency of systems.…”
Section: Related Workmentioning
confidence: 99%